2023
DOI: 10.3390/su152215858
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Impact of Potassium on Growth, Photosynthetic Performance, and Nutritional Status of Lemon Trees (cv. Adamopoulou) Grafted onto Sour Orange and Volkamer Lemon Rootstocks

Ioannis E. Papadakis,
Evangelia-Vasiliki Ladikou,
Alexia Oikonomou
et al.

Abstract: (1) Background: This study investigates the effects of potassium (K) and rootstock on the growth, photosynthetic activity, and mineral nutrition of lemon trees; (2) Methods: Lemon trees (cv. Adamopoulou) grafted onto sour orange (Citrus aurantium) (SO) or Volkamer lemon (Citrus volkameriana) (VL) rootstock were cultivated hydroponically under 0.00, 0.75, 1.50, 3.00, and 6.00 mM K. Plant growth and nutrition parameters, as well as leaf photosynthetic rate, stomatal conductance, transpiration rate, intracellular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 50 publications
0
1
0
Order By: Relevance
“…Stomatal and non-stomatal factors are the two categories of factors that in uence the rate of photosynthetic activity in plants. Papadakis et al (2023) suggested that variations in stomatal conductance and intercellular carbon dioxide concentration should be examined concurrently in order to assess the factors that in uence the rate of photosynthetic activity of plants.…”
Section: Discussionmentioning
confidence: 99%
“…Stomatal and non-stomatal factors are the two categories of factors that in uence the rate of photosynthetic activity in plants. Papadakis et al (2023) suggested that variations in stomatal conductance and intercellular carbon dioxide concentration should be examined concurrently in order to assess the factors that in uence the rate of photosynthetic activity of plants.…”
Section: Discussionmentioning
confidence: 99%